Association between Smoking and the Risk of Incidence and Progression of Osteoarthritis: A Systematic Review - Pasambuna, Annisa M.S.; Arifuddin, Abdul Mubdi Ardiansar; Bausat, Arman; Chaniago, Hendrian; Rumlawan, Sarinah Mandella (Journal of Asian-african Focus in Health, 2026)
Osteoarthritis is a degenerative joint disease that is one of the main causes of pain and disability in the adult population. Smoking has long been associated with various chronic diseases, but evidence regarding the specificity of osteoarthritis incidence still shows mixed results. This study aims to establish the relationship between cigarette smoke exposure and osteoarthritis incidence through a systematic approach. This study is a systematic observational study compiled in accordance with the PRISMA 2020 guidelines. A literature search was conducted on several scientific data bases to obtain relevant studies. Studies that met the inclusion criteria were systematically analyzed. Data synthesis was performed narratively by comparing the results and direction of the relationship between studies. The synthesis of the results showed that most studies reported a trend of increased risk of osteoarthritis in individuals exposed to cigarette smoke, although the reported effect sizes varied. The results of the synthesis of six studies showed that most studies pointed to an association between smoking and osteoarthritis, but the magnitude and direction of the association between studies were heterogeneous. This systematic review shows a trend of an association between cigarette smoke exposure and osteoarthritis incidence. A narrative synthesis of the available studies indicates an association between cigarette exposure and osteoarthritis. This systematic review suggests a trend toward an association between smoking exposure and osteoarthritis. However, evidence regarding disease progression remains variable and inconsistent.